Repeated Transcranial Magnetic Stimulation–Induced Motor Evoked Potentials Correlate With the Subject-Specific Serum Metabolic Profile of Creatine. Issue 3 (May 2019) - Kallioniemi, Elisa; Kärkkäinen, Olli; Määttä, Sara; Könönen, Mervi; Kivimäki, Petri; Kaarre, Outi; Velagapudi, Vidya; Kekkonen, Virve; Lehto, Soili M.; Laukkanen, Eila; Tolmunen, Tommi
Abstract : Purpose: Transcranial magnetic stimulation–induced motor responses have been considered to mainly reflect the electrophysiological characteristics of the central motor system. However, certain motor phenomena, such as the magnitude of repetition suppression measured with motor evoked potentials (MEPs), could also in part be influenced by metabolic processes in the peripheral muscles and in both the peripheral and central nervous system. Repetition suppression is an inhibitory phenomenon in which the amplitude of MEP decreases in comparison to that of the first MEP in a train of transcranial magnetic stimulation pulses. This study aimed to identify possible metabolic processes influencing repetition suppression. Methods: The metabolic profiles from serum samples and repetition suppression from the right abductor pollicis brevis muscle were measured in 73 subjects (37 female subjects). Repetition suppression was measured using trains of transcranial magnetic stimulation stimuli consisting of 4 identical single pulses at 1-second intervals. The trains were repeated every 20 seconds, and 30 trains were given with a stimulation intensity of 120% of the resting motor threshold of the abductor pollicis brevis. Thus, a total of 120 stimuli were administered. Results: The main finding was a significant negative relationship between serum creatine levels and the magnitude of repetition suppression (standardized β coefficient (β) = −0.43; P < 0.001). In other words, higher creatine levels corresponded to a smaller decrement in the MEP amplitude in response to repetition. When MEPs were not repeated, no relationship was observed (β = 0.09; P = 0.454). Creatine is used to form phosphocreatine, which in turn is needed to resynthesize adenosine triphosphate from adenosine diphosphate in situations requiring high amounts of energy in muscles and neural cells. Conclusions: For the first time, this study demonstrated a connection between repeated MEPs and peripheral serum metabolites linked to muscle function. These findings could explain some of the intersubject variability commonly observed in MEPs when the pulses are repeated. Abstract : Supplemental Digital Content is Available in the Text.